Ad Hoc Networks Third International ICST Conference, ADHOCNETS 2011, Paris, France, September 21-23, 2011, Revised Selected Papers - Simplot-Ryl, David; Dias de Amorim, Marcelo; Giordano, Silvia; Helmy, Ahmed; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This volume constitutes the refereed proceedings of the Third International ICST Conference, ADHOCNETS 2011, held in Paris, France, in September 2011. The 15 revised full papers - selected from 42 submissions - and the 2 invited papers cover several fundamental aspects of ad hoc networking, including security, quality of service, radio and spectrum analysis, mobility, energy efficiency, and deployment. They are organized in topical sections on security and QoS, WSN development and evaluation, radio and spectrum analysis, mobile WSNs, mobile ad hoc networks, and energy.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Data encryption (Computer science).; Computer software; Computer simulation; Information Systems; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Data Encryption; System Performance and Evaluation; Simulation and Modeling